Availability and utilisation of physician-based pre-hospital critical care support to the NHS ambulance service in England, Wales and Northern Ireland. Issue 3 (21st March 2011) - Hyde, Philip; Mackenzie, Rod; Ng, Gail; Reid, Cliff; Pearson, Gale
Abstract : Background: Every day throughout the UK, ambulance services seek medical assistance in providing critically ill or injured patients with pre-hospital care. Objective: To identify the current availability and utilisation of physician-based pre-hospital critical care capability across England, Wales and Northern Ireland. Design: A postal and telephone survey was undertaken between April and December 2009 of all 13 regional NHS ambulance services, 17 air ambulance charities, 34 organisations affiliated to the British Association for Immediate Care and 215 type 1 emergency departments in England, Wales and Northern Ireland. The survey focused on the availability and use of physician-based pre-hospital critical care support. Results: The response rate was 100%. Although nine NHS ambulance services recorded physician attendance at 6155 incidents, few could quantify doctor availability and utilisation. All but one of the British Association for Immediate Care organisations deployed 'only when available' and only 45% of active doctors could provide critical care support. Eleven air ambulance services (65%) operated with a doctor but only 5 (29%) operated 7 days a week. Fifty-nine EDs (27%) had a pre-hospital team but only 5 (2%) had 24 h deployable critical care capability and none were used regularly. Conclusion: There is wide geographical and diurnal variability in availability and utilisation of physician-based pre-hospital critical care support. Only London ambulance service has access to NHS-commissioned 24 h physician-based pre-hospital critical care support. Throughout the rest of the UK, extensive use is made of volunteer doctors and charity sector providers of varying availability and capability.